Sherlock Holmes through time: The secret behind Arthur Conan Doyle’s enduring success - Saliyeva Raykhona (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
For generations, people have been captivated by Sherlock Holmes, a character who is more than a fictional detective. This paper explores why Holmes is still so popular today, how Arthur Conan Doyle crafted a character who remains relevant, and some of his methods. Despite being inspired by real detective techniques and individuals such as Dr. Joseph Bell, Holmes is a fictional character whose remarkable deduction technique was not fiction. The warmth and humor of the relationship between Holmes and Watson are another source of the secret popularity of the stories. Holmes's popularity has endured through the decades because of the films that have brought him back to life. This project uncovers the mystery of Sherlock Holmes' enduring popularity by examining media, character relationships, and history.